Diaper need is associated with risk for food insecurity in a statewide sample of participants in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) - Belarmino, Emily H. (Prev Med Rep, 2021)
Diaper need is a form of material hardship that acutely affects families with young children, is not currently addressed by US antipoverty programs, and has received little public or scientific attention. This study examined the association between diaper need and risk for food insecurity in a statewide sample of participants in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Families enrolled in Vermont WIC in August 2019 were invited to an online survey that included questions related to diaper need and food need. Pearson’s Chi-square tests were used to examine the association between diaper need and risk for food insecurity measured by the Hunger Vital Sign Tool, and the associations between diaper need and other household factors. Follow-up questions asked those with diaper need what they do when they run out of diapers and those without diaper need how they access enough diapers. Responses to these questions were tabulated. Complete data were available for 501 households. Over half (52.3%) were at risk for food insecurity and nearly one-third (32.5%) reported diaper need. Households with diaper need were more likely to be at risk for food insecurity than those without diaper need (p < 0.001). Strategies to avoid running out of diapers included borrowing, stretching supplies, seeking diapers from an agency or support organization, switching to cloth or underwear, and buying on credit. Interventions that address diaper need may alleviate hardship and support health equity among families with young children.